Métodos de manejo para Duponchelia fovealis Zeller (Lepidoptera : Crambidae) na cultura do morangueiro - Pirovani, Victor Dias (2016)
The exotic caterpillar strawberry, Duponchelia fovealis Zeller (Lepidoptera: Crambidae) is causing heavy losses in Brazil and in the Espírito Santo state since its introduction. Thus, it is necessary that management methods are studied for the control of